2015
DOI: 10.11113/jt.v77.6871
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Design for Maintainability Imperatives to Achieve Cost Effective Building Maintenance: A Delphi Study

Abstract: Incorporating maintainability during the building design is essential to increase overall performance of the building including quality and cost as; the management and operation process of facilities can have a significant impact on cost, health and safety, energy and quality. As a result, a more effective and efficient building facility will be turned over during the post occupancy stage. Literature review reveals that there is a need to implement maintainability during the building design phase; mainly due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Quality standard verification of maintenance works and spare parts to meet quality standards level is a method to solve low-quality maintenance work. Maintenance management should always give important consideration for the procurement of quality to fulfil the requirements of excellent specifications (Ganisen et al, 2015a;Omar et al, 2107;Au-Yong et al, 2017;Soh et al, 2019). Also, Au- Yong et al (2017) recommended that the use of spare parts of low quality must be avoided.…”
Section: Effective Managementmentioning
confidence: 99%
“…Quality standard verification of maintenance works and spare parts to meet quality standards level is a method to solve low-quality maintenance work. Maintenance management should always give important consideration for the procurement of quality to fulfil the requirements of excellent specifications (Ganisen et al, 2015a;Omar et al, 2107;Au-Yong et al, 2017;Soh et al, 2019). Also, Au- Yong et al (2017) recommended that the use of spare parts of low quality must be avoided.…”
Section: Effective Managementmentioning
confidence: 99%
“…Another factor that several authors identified Meier and Russell (2000), Fitzgerald (2001), Molinari (2002), de Silva et al (2004), Ganisen et al (2015) is maintainability, namely the ease of performing maintenance operations, which helps to eliminate maintenance costs, reduces downtime, and increases safety. As such, buildings should be designed taking this factor into account.…”
Section: Survey Methodology – An Overview Of Building Maintenancementioning
confidence: 99%
“…This strategy is about involving the facility manager, or facility management knowledge in the design phase. Important criteria in designing for maintainability is durability of building materials, easy access and performance of cleaning, repairs and replacement of materials and components [99]. Only one paper addresses the environmental benefits of applying this strategy showing that the use of durable materials show promise in terms of reducing embodied impacts.…”
Section: Design For Maintainabilitymentioning
confidence: 99%